LAPAROSCOPIC CHOLECYSTECTOMY: AN EARLY EXPERIENCE AT AYUB TEACHING HOSPITAL ABBOTTABAD - Mufti, Tariq Saeed; Ahmad, Sajjad; Naveed, Danish; Akbar, Muhammad; Zafar, Arshad (Journal of Ayub Medical College Abbottabad, 2007)
Background: Laparoscopic Cholecystectomy first introduced in 1987, is becoming more and more popular and now it has become gold standard in symptomatic gallstone disease. The current descriptive study is carried out in Department of General Surgery, Ayub Teaching hospital, Abbottabad to evaluate the result of Laparoscopic Cholecystectomy in symptomatic gallstones disease in our set up with special emphasis on complication rate, morbidity and mortality. Methods: The data of all patients who underwent Laparoscopic Cholecystectomy form January to December 2007 was entered in standardized proforma and analysed on SPSS 10. Results: Out of 60 patients, 51 (85%) were female and 9 (15%) were males; the age range from 17 to 65 years mean age being 40.30 years, majority were in age 30-40 years group. Two (3.3%) patients had bile leak, 1 (1.3%) patient developed port site wound infection 1 (1.3%) patient developed collection in pouch of Morrison and in 1 (1.3%) patient stone were recovered from the epigastric port site wound. There was no bile duct or colonic injuries. The conversion rate was 5%. There was no mortality. Conclusion: Laparoscopic cholecystectomy is a safe and effective treatment for gall stone disease and is up to the accepted standard in our set up as compared to national and international data. Key Words; Laparoscopic Cholecystectomy, morbidity, mortality.